Di Gi Charat. Vol. 2 - Donbo, Koge; Jones, Gerard; Morimoto, Mari; Ristaino, Andy (Viz graphic novel, 2003)
The Dark Gema Gema Gang, led by eight-year old Piyoko, has come to town, intending to drive Digiko to distraction, but Digiko and her pals are so busy fighting amongst themselves to even notice.